TALK SHOW MARIO TEGUH GOLDEN WAYS â€œGALAU NASIBâ€ (Study of Grammatical Aspect) - Aditya, Silvia Erlin (JURNAL LITERARY CRITICISM, 2016)
The article talks about the analysis of grammatical aspect in talk show mario teguh golden ways galau nasib episode. The research methodology is descriptive qualitative. Data in the form of document were collected through transcription of the talk show that served on 4th may 2014. Data processing technique is contents analysis .The data were analysed through discourse analysis approach in order to find out the grammatical aspect used. The findings show reference, substitution, ellipsis and conjunction were  grammatical aspect that have been identified. Reference is dominated grammatical aspect that used in this talk show, then conjunction, ellipsis and substitution. Keywords: Discourse Analysis, grammatical aspect, Talk show, Mario Teguh.